Peningkatan Literasi Hak Cipta dan Kesiapan Monetisasi Konten Digital Siswa SMK Melalui Workshop Partisipatif: Enhancing Copyright Literacy and Readiness for Monetizing Digital Content Among Vocational School Students Through Participatory Workshops - Eling Wening Pangestu; Siti Syifazalia Anjariska Putri; Teguh Budi Trisnanto; Meyla Tazqiya Rakhma; Vellyana Paraswati; Syaifuddin Muhammad Mirza (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Digital content production in vocational schools is growing rapidly, but this has not been accompanied by an adequate understanding of copyright, the use of legal assets, and readiness for monetization. This situation has the potential to lead to copyright infringement and to hinder students' economic opportunities for creativity. This community service activity aims to improve copyright literacy, the application of legal elements in content production, and digital monetization readiness among students and teachers at SMKN 1, SMKN 7, and SMKN 4 Bandar Lampung through participatory workshops grounded in media production practices. The implementation method used a workshop approach with one-group pre-test post-test evaluation, supplemented by artifact analysis and observation of the production process to assess changes in students' knowledge and practices. The results of the activity showed a significant increase in all knowledge domains, with pre-test scores of 57.7–64.7 increasing to 89.1–94.0 and high effectiveness based on N-Gain (0.75–0.83). Analysis of the work shows that students are able to apply attribution more accurately, select legally licensed assets, compile metadata more systematically, and exercise greater caution when using third-party material. The direct benefits for partners include increased student competence in producing legally safe digital content that is better prepared for publication on digital platforms. Teachers also gain practical models for integrating into productive learning. This activity demonstrates that practice-based workshops are effective in strengthening the legal, technical, and digital economic readiness competencies of vocational students.